Marks' basic medical biochemistry a clinical approach - Lieberman, Michael; Peet, Alisa (Wolters Kluwer Health, 2023)
Marks' Basic Medical Biochemistry: A Clinical Approach, 6th Edition links biochemistry to physiology and pathophysiology, empowering students to confidently apply fundamental concepts to the practice of medicine from diagnosing patients to recommending effective treatments. This proven, application-centered approach builds biochemical coverage around related clinical concepts to anchor students' understanding to a clinical context from day one. Intuitively organized chapters center on hypothetical patient vignettes to emphasize clinical applications, and helpful icons, images, and review questions make complex concepts easier to grasp.